Concept evaluation dilemma: Presentation effect on product concept evaluation in the new product development (NPD) process. Issue 2 (3rd April 2023) - Kwon, Jieun; Kudrowitz, Barry
ABSTRACT: New Product Design (NPD) process involves multiple phases in which a designer or an engineer shares their idea through verbal and visual presentation. Specifically, during the early concept selection phase, designers often pitch their ideas to peers, investors, and consumers to communicate their developing ideas. During this process, the audiences' perception of the concept can be influenced by how it was presented. This article examines a) if the presence of visual aids can influence the concept evaluation, b) if the verbal presentation quality can affect how the concept value is perceived, and c) if product design experts can see the value of a concept beyond how it was presented. The results showed that whether visual or verbal, presentation quality can affect how the audience evaluates the concept that is being presented. In addition, contrary to what was expected, it was found that the design experts were more influenced by the presentation quality than the non-experts.